Literature Review: From Grain to Functional Food: Physicochemical Properties and Processing Applications of Pearl Millet (Pennisetum glaucum) - Clarinda Djuali (JFCN: Journal of Food, Culinary, and Nutrition, 2026)
Pearl millet is the sixth most important cereal grain consumed by approximately one-third of the global population and has long served as a staple food for many communities worldwide. However, this cereal is still often perceived as a food for lower socioeconomic groups and is therefore rarely included in the diets of elite populations. In fact, pearl millet contains a wide range of functional components that remain largely underrecognized. This review aims to provide a comprehensive overview of pearl millet, covering its physicochemical characteristics, nutritional and functional components, as well as processing technologies. The crop’s tolerance to drought, low-fertility soils, and extreme temperatures makes pearl millet more resilient that other cereal crops such as wheat and rice, thereby positioning it as a superior option for food security. In West Sulawesi, pearl millet is used in traditional foods such as porridge and cakes, and it can also be processed into various products including couscous, bread, mnin-alcoholic beveragess, and beer. Prior to consumption or use in food products, pearl millet requires processing due to its bitter taste and susceptibility to rancidity. Processing technologies such as fermentation, extrusion, and flour production enhance the nutritional value and functional properties of pearl millet.